Analysis Of The Particulate Matter Concentrations PM2.5 And The Weather Variables Of Precipitation And Temperature In The Dry Period (2018) And Rainy Period (2019) In The Universidad Libre- Bogotá Campus - Acosta Nieto, Maria Fernanda; Altamar Consuegra, Astrid del Socorro; Aragón Moreno, Juan Antonio (Ingeniería Solidaria, 2021)
Introduction: This paper is the outcome of the research on the determination of the concentration of particulatematter PM2.5, estimating the influence of temperature and precipitation, developed at the Universidad Libre, at the Bogotá campus during the years 2018-2019.Problem:[PM2,5] concentration near the University, Bosque Popular campus has increasedin recent years, influenced by mobile sources,in spite of the green zones.Objective: To determine the relationship of the particulate matter with the Precipitation and Temperature as meteorological variables, and the influence of the contributing sources of PM2.5 in the studied area.Methodology: For the determination of [PM2.5] a WilBur model low volume sampler was used. The meteorological data were obtained from the Bogotá Air Quality Monitoring Network of the Secretariat of the Environment. Software such as ArcGis, WRPLOT and MiniTab were used for the graphical representation of the results.Results: The average [PM2.5] for the dry and wet season were 9.03 and 19.22 μm/m3. For the meteorological variables, a precipitation of 40.4 and 373.6mm, and temperature of 14.3 and 15.32°C, respectively, were obtained.Conclusion: There is a low relationship between meteorological variables and [PM2.5] in both monitoring sea-sons, however, the concentration performance is similar to that found in the references.Originality: PM2.5 sampling in both seasons within the Universidad Libre, cataloged as a background area.Limitations:The monitoring time was during the months of July and August for the year 2018 and March to May in the year 2019.